A Tapestry of Tongues: A Novel Provenance Approach for Arabic Linguistic Styles and Lineage Tracing - Sabour, Adel; Ali, Mohamed; Hendawi, Abdeltawab (Journal of Quranic Sciences and Research, 2024)
This research introduces a novel framework for analyzing Arabic linguistic styles, focusing on the Quran as a case study. Unlike previous studies that often focus on a single style or regional variations, ours examines the unique features of multiple styles within the single text. Our approach addresses inconsistencies in Arabic character representation. This creates a standardized format for analyzing the text, ensuring consistent results. This research utilizes a Provenance Tracker to connect different linguistic styles and document their lineage through narrators By analyzing a single text that showcases multiple styles, this study paves the way for identifying the unique characteristics of each linguistic style. Additionally, the research develops algorithms to map individual letters, words, and diacritics between each style. Moreover, this allows for in-depth linguistic analysis, revealing the unique characteristics that define each style. This opens new avenues for research into the Arabic language’s rich stylistic diversity.